BATIK DERMAYON SUATU KEINDAHAN DALAM SEBUAH KETERBATASAN - Muh. Arif Jati Purnomo (Institut Seni Indonesia Surakarta, 2011)
IndramayuÂ batik or people used to call the Dermayon batik is one of the coastal batik that had its own uniqueness and beauty of the coastal batik among others. One hallmark of this Dermayon batik is the emergence of technique